Finite elements in analysis and design (Elsevier, 1985)
"An International journal for innovations in computational methodology and application."
Keywords: Finite element method : Periodicals; Engineering design : Data processing : Periodicals; Computer-aided design : Periodicals; Éléments finis, Méthode des : Périodiques; Conception technique : Informatique : Périodiques; Conception assistée par ordinateur : Périodiques